Cytokines trigger disruption of endothelium barrier function and p38 MAP kinase activation in BMPR2-silenced human lung microvascular endothelial cells. (October 2019) - Tielemans, Birger; Stoian, Leanda; Gijsbers, Rik; Michiels, Annelies; Wagenaar, Allard; Farre Marti, Ricard; Belge, Catharina; Delcroix, Marion; Quarck, Rozenn
The bone morphogenetic protein receptor II (BMPRII) signaling pathway is impaired in pulmonary arterial hypertension and mutations in the BMPR2 gene have been observed in both heritable and idiopathic pulmonary arterial hypertension. However, all BMPR2 mutation carriers do not develop pulmonary arterial hypertension, and inflammation could trigger the development of the disease in BMPR2 mutation carriers. Circulating levels and/or lung tissue expression of cytokines such as tumor necrosis factor-α or interleukin-18 are elevated in patients with pulmonary arterial hypertension and could be involved in the pathogenesis of pulmonary arterial hypertension. We consequently hypothesized that cytokines could trigger endothelial dysfunction in addition to impaired BMPRII signaling. Our aim was to determine whether impairment of BMPRII signaling might affect endothelium barrier function and adhesiveness to monocytes, in response to cytokines. BMPR2 was silenced in human lung microvascular endothelial cells (HLMVECs) using lentiviral vectors encoding microRNA-based hairpins. Effects of tumor necrosis factor-α and interleukin-18 on HLMVEC adhesiveness to the human monocyte cell line THP-1, adhesion molecule expression, endothelial barrier function and activation of P38MAPK were investigated in vitro. Stable BMPR2 silencing in HLMVECs resulted in impaired endothelial barrier function and constitutive activation of P38MAPK. Adhesiveness of BMPR2 -silenced HLMVECs to THP-1 cells was enhanced by tumor necrosis factor-α and interleukin-18 through ICAM-1 adhesion molecule. Interestingly, tumor necrosis factor-α induced activation of P38MAPK and disrupted endothelial barrier function in BMPR2 -silenced HLMVECs. Altogether, our findings showed that stable BMPR2 silencing resulted in impaired endothelial barrier function and activation of P38MAPK in HLMVECs. In BMPR2 -silenced HLMVECs, cytokines enhanced adhesiveness capacities, activation of P38MAPK and impaired endothelial barrier function suggesting that cytokines could trigger the development of pulmonary arterial hypertension in a context of impaired BMPRII signaling pathway.